Annihilators through fault injection analysis on selected stream ciphers - Omar @ Othman, Wan Zariman (2019)
Algebraic attacks on stream cipher are important in cryptanalysis to both design- ers and attackers. Generally, complexity of an algebraic attack will increase as the degree of an equation increases. In conducting this attack, we aim to decrease the degree of the targeted boolean equation by constructing low degree annihilator equa- tion(s). We adopt the Fault Injection Analysis (FIA) methodology to achieve our objectives. In this study, we found annihilator(s) through FIA (inject with value of one (1)) on boolean function of selected stream ciphers. With these injected boolean functions, we proceed to utilize Hao's method to find new annihilator(s). Then we obtained new annihilator(s) on boolean function of Pomaranch, Grain v0 and also LILI-128 stream ciphers. As a result, these newly identified annihilators success- fully reduce the complexity of the published boolean function to guess the initial secret key. It also provides much needed information on the security of these se- lected stream ciphers with respect to FIA.